تعليم مهارة القراءة بتحويل الشفرة - Jaka Imam Mahesa Wijaya (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2018)
Abstract : The aims of the research is adressing the types of code switching in the qiraah learning in the Arabic Teaching Department of UIN Imam Bonjol Padang. The research method is case study in the class room Arabic teaching. because Addressing and triggering; type, triggering it factor, triggering factor of codes are contribution for Arabic teaching. The research finding showed code switching used by the lecturer is correlated to the part of sentences; words and pharses. The code switching is also could be related to phonology, voucaboulary and grammar. The lecturer used to switch from Arabic to Bahasa and from Bahasa to Arabic. In the context of the types of code switching, the productive code switching, the situational code switching, intersentential code switching, the external code switching, metpho rical code switching, intrasentential code switching were found. The trigerring factor of the code switching are; (1) the state of the speaker and the listener; (2) the appearing of third figure outside the speaker and the listener. The code switching contributed in the extents of (1) explaining the learning content; (2) confriming the meaning (3) evaluating student understanding.